2016
DOI: 10.1186/s12909-016-0718-x
|View full text |Cite
|
Sign up to set email alerts
|

The validity of a professional competence tool for physiotherapy students in simulation-based clinical education: a Rasch analysis

Abstract: BackgroundDespite the recent widespread adoption of simulation in clinical education in physiotherapy, there is a lack of validated tools for assessment in this setting. The Assessment of Physiotherapy Practice (APP) is a comprehensive tool used in clinical placement settings in Australia to measure professional competence of physiotherapy students. The aim of the study was to evaluate the validity of the APP for student assessment in simulation settings.MethodsA total of 1260 APPs were collected, 971 from stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…Assessing clinical competencies is important when preparing PT students for clinical practice [ 35 37 ]. A range of tools has been used to evaluate clinical competencies [ 38 41 ]. The literature on the assessment of the clinical performance of physiotherapy students in the South American context is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing clinical competencies is important when preparing PT students for clinical practice [ 35 37 ]. A range of tools has been used to evaluate clinical competencies [ 38 41 ]. The literature on the assessment of the clinical performance of physiotherapy students in the South American context is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, other items of the APP such as "demonstrate commitment to learning" are not within the scope of the APSPT. Similar to this study the APP has been validated using Rasch analysis and the authors have reported adequate structural validity of the APP [37]. Future studies might set out to test the correlation between the APSPT and the APP's subscale of procedural skills to further validate the APSPT.…”
Section: Discussion Of Main Resultsmentioning
confidence: 62%
“…Recently Judd and colleagues [37] have reported on the validity of the Assessment of Physiotherapy Practice (APP), which is a professional competence tool for physiotherapy students in simulation based clinical. The latent dimension of this tool (i.e.…”
Section: Discussion Of Main Resultsmentioning
confidence: 99%
“…Although research on clinical simulation as a pedagogic strategy in physiotherapy has increased, it is necessary to continue with reports of this type to enhance student training in therapeutic interaction and thus improve decision-making in the clinical reality (24).…”
Section: Discussionmentioning
confidence: 99%